New olfactometric findings in Parkinson's disease. (1st February 2017) - Passali, G.C.; Bove, F.; Vargiu, L.; Bentivoglio, A.R.; Anzivino, R.; De Corso, E.; Galli, J.; Rigante, M.; Pandolfini, M.; Sergi, B.; Giuliani, M.; Cianfrone, F.; et al.
Abstract : Objectives: To investigate in Parkinson's disease‐affected patients a correlation between hyposmia and gastrointestinal dysfunction and their possible identical etiopathogenesis. Design: Retrospective cohort study. Setting: ENT and neurology departments (Gemelli Hospital, Rome, Italy). Participants: A total of 78 patients with diagnosis of PD according to the UK Brain Bank criteria. Inclusion criteria: informed consent and olfactory testing executed; exclusion criteria: signs of dementia according to the DSM‐IV criteria; Mini Mental State Examination score ≤26; head trauma; central neurological disorders, nasal or systemic diseases potentially affecting olfactory function. Motor condition was assessed by means of Hoehn and Yahr staging and by section III of the Unified PD Rating Scale, performed off and on medications. Main outcome measures: The patients underwent olfactory evaluation (TDI score), after rhinomanometry with nasal decongestion. A total of 25 non‐motor symptoms were evaluated through an interview. Results: Olfactory dysfunction was objectively found in 91.0% of patients, a percentage higher than the subjective hyposmia reported (55.1%) P = 0.0001. Seven patients (9.0%) were normosmic, 49 (62.8%) hyposmic and 22 (28.2%) anosmic. Subjective hyposmia, constipation, bloating and dyspepsia differed across groups, being higher in anosmic and hyposmic ones than in the normosmic group. P value was ≤0.05 for each symptom. Despite the original results, this study has the limitation of being based on subjective ratings by a relatively limited group of patients. Conclusions: Hyposmia and gastrointestinal symptoms are correlated, and this would support a possible common origin; the CNS could be reached through two different pathways, both starting in the peripheral nervous system.